2011
DOI: 10.1088/0143-0807/32/4/004
|View full text |Cite
|
Sign up to set email alerts
|

Optical refraction in silver: counterposition, negative phase velocity and orthogonal phase velocity

Abstract: Complex behaviour associated with metamaterials can arise even in commonplace isotropic dielectric materials. We demonstrate how silver, for example, can support negative phase velocity and counterposition, but not negative refraction, at optical frequencies. The transition from positive to negative phase velocity is not accompanied by remarkable changes in the Abraham and Minkowski momentum densities. In particular, orthogonal phase velocity is associated with nonzero Abraham and Minkowski momentum densities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…It was also predicted for bulk metals in case of specially polarized incident light [26,28]. However, as far as we know, negative refraction of phase velocity in conventional media has never been reported before.…”
Section: Metallic Prismmentioning
confidence: 61%
“…It was also predicted for bulk metals in case of specially polarized incident light [26,28]. However, as far as we know, negative refraction of phase velocity in conventional media has never been reported before.…”
Section: Metallic Prismmentioning
confidence: 61%
“…To be more specific, we consider a circular cylinder of silver metal with the relative permittivity written as [14] …”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…For example, it gives low power dissipation at optical frequency range, and hence, the apple of eyes of metamaterial designers. It can be used as special filter [10], and also, many innovative concepts like counterposition [11], transition from positive to negative phase velocity [12], orthogonal phase velocity [13], etc., are observed in the case of silver metal at optical frequencies [14].…”
Section: Introductionmentioning
confidence: 85%
“…[9] In the case of L-nihility medium engineered from silver metal, it is observed that the real part of permittivity of silver metal becomes zero at certain frequency. [10] Strip periodic surfaces possess fascinating and novel characteristics that can be employed in antenna-related applications.…”
Section: Introductionmentioning
confidence: 99%